C-class functions on fixed and common fixed point results for cyclic mappings of Omega-distance - Ansari, Arslan Hojat Hojat; Shatanawi, Wasfi (Nonlinear Analysis: Modelling and Control, 2017)
In this paper, we derive and formulate many fixed point results of cyclic form under contractive conditions based on implicit relations in the setting of Ω-distance. Our results improve and generalize many existing results in the literature. Also, we introduce an example to show the validity of our main result.